2‐Deoxy Glucose Modulates Expression and Biological Activity of VEGF in a SIRT‐1 Dependent Mechanism. Issue 2 (27th June 2016) - Kunhiraman, Haritha; Edatt, Lincy; Thekkeveedu, Sruthi; Poyyakkara, Aswini; Raveendran, Viji; Kiran, Manikantan Syamala; Sudhakaran, Perumana; Kumar, Sameer V.B.
ABSTRACT: Reprogramming of energy metabolism particularly switching over of cells to aerobic glycolysis leading to accumulation of lactate is a hallmark of cancer. Lactate can induce angiogenesis, an important process underlying tumor growth and metastasis. VEGF is one of the most important cytokines which regulate this process and the present study was designed to examine if blocking glycolytic pathway in tumor cells can affect its angiogenic potency with respect to VEGF. For this, the expression and biological activity of VEGF synthesized and secreted by tumor derived cell lines in the presence or absence of 2‐deoxy glucose (2‐DG), an inhibitor of glycolysis was determined. The results suggested that inhibition of glycolysis using sub‐lethal doses of 2‐DG down‐regulated the expression of VEGF and also significantly reduced its biological activity. Further mechanistic studies revealed that the down regulation of VEGF gene expression by 2‐DG was due to an increase in SIRT‐1 activity and the reduced biological activity was found to be due to an increase in the PAR modification of VEGF. Activity of SIRT‐1 and PAR modification of VEGF in turn, was found to be correlated to the cellular NAD + levels. The results presented here therefore suggest that treatment of cancer cells with 2‐DG can significantly reduce its overall angiogenic potency through transcriptional and post‐translational mechanisms. J. Cell. Biochem. 118: 252–262, 2017. © 2016 Wiley Periodicals, Inc. Abstract : 2‐DG at sub‐lethal concentration that fails to induce ER stress response, cause partial inhibition of glycolysis and a concomitant increase in the cellular NAD + level in the NAD + /NADH pool. Increased NAD + levels cause activation of SIRT‐1 which in turn causes a down regulation of VEGF expression. Higher levels of NAD + also cause an increase in poly ADP ribosylation of VEGF which in turn causes a reduction in biological activity of VEGF production. 2‐DG thereby reduces the angiogenic potency of tumor cells by reducing the production and biological activity of VEGF secreted by them, in a SIRT‐1 dependent mechanism.